Agroforestry Berbasis On Farm Riset dalam Mengantispasi Perubahan Iklim di Desa Pudaria Jaya Kecamatan Moramo Kabupaten Konawe Selatan: Agroforestry On Farm Research in Anticipating Climate Change at Pudaria Jaya Village, Moramo District, South Konawe Regency - Basrudin; Arafah, Nur; fitriani, Vivi; Indriyani, Lies; Bana, Sahindomi; Pujirahayu, Niken; Uslinawaty, Zakiah; Hasani, Umar Ode; Hadjar, Nur Hayati; Ahmaliun, La De (Program Studi Ilmu Tanah, Fakultas Pertanian, Universitas Jember, 2023)
Agroforestry emerged as a result of land conversion problems caused by population growth. Conversion of forest land into agricultural land will result in climate change. In anticipating climate change, it is necessary to provide outreach activities to the community regarding the integration of agroforestry systems in land use. Integration between forestry crops and agricultural crops is seen as an appropriate method for reducing food scarcity while also providing environmental benefits. Agroforestry is primarily expected to help optimize the results of a form of sustainable land use in order to guarantee and improve people's living needs, and can increase the carrying capacity of human ecology, especially in rural areas. The implementation of an on-farm research-based agroforestry system is carried out on community land. The aim of the community service program is to resolve problems faced by partners by conducting outreach and training regarding the implementation of agroforestry systems to anticipate climate change. The expected impact of this program is that the community will have understanding and expertise in mitigating climate change through the integration of agroforestry systems. The method of implementing the service program is socialization, discussion and training with the community. The expected target of community service is increasing understanding of climate change mitigation through the implementation of agroforestry systems.